(S)-norketamine and (2S,6S)-hydroxynorketamine exert potent antidepressant-like effects in a chronic corticosterone-induced mouse model of depression - Yokoyama, Rei; Higuchi, Momoko; Tanabe, Wataru; Tsukada, Shinji; Naito, Megumi; Yamaguchi, Takumi; Chen, Lu; Kasai, Atsushi; Seiriki, Kaoru; Nakazawa, Takanobu; Nakagawa, Shinsaku; Hashimoto, Kenji; et al. (Pharmacology, biochemistry and behavior, 2020)
Clinical and preclinical studies have shown that the N-methyl-d-aspartate receptor antagonist ketamine exerts rapid and long-lasting antidepressant effects. Although ketamine metabolites might also have potential antidepressant properties, controversial results have been reported for (2R,6R)-hydroxynorketamine ((2R,6R)-HNK) in particular, and there is little information regarding the effects of other ketamine metabolites. Here we aimed to compare the effects of (R)-norketamine ((R)-NK), (S)-NK, (2R,6R)-HNK, and (2S,6S)-HNK in a mouse model of depression induced by chronic corticosterone (CORT) injection. None of the ketamine metabolites at doses up to 20 mg/kg showed antidepressant-like activity in naïve male C57BL6/J mice. Chronic CORT treatment increased immobility in the forced swim test and caused anhedonic-like behaviors in the female encounter test. A single administration of (S)-NK and (2S,6S)-HNK dose-dependently reduced the enhanced immobility at 30 min after injection in chronic CORT-treated mice, while (R)-NK or (2R,6R)-HNK did not. Additionally, (S)-NK and (2S,6S)-HNK, but not (R)-NK or (2R,6R)-HNK, improved chronic CORT-induced anhedonia at 24 h after the injection. These results suggest that (S)-ketamine metabolites (S)-NK and (2S,6S)-HNK have potent acute and sustained antidepressant effects in rodents. •Chronic corticosterone induced a depression-like state and anhedonia in mice.•No ketamine metabolite showed antidepressant effects in naïve C57BL/6J mice.•(S)-NK and (2S,6S)-HNK reversed the enhanced immobility in the forced swim test.•(S)-NK and (2S,6S)-HNK improved impaired female preferences.